THE COGNITIVE REVOLUTION: RECLAIMING LANGUAGE FROM MYTH TO REAWAKEN HUMAN AGENCY - Mahmudjon Kuchkarov; Marufjon Kuchkarov (World Scientific Research Journal, 2025)
This study challenges conventional narratives of linguistic origins through Odam Tili (OT) theory [1], proposing that human language emerged as an embodied biological response to environmental stimuli rather than divine instruction. Contrasting with religious traditions [2,3], we demonstrate how speech organically arose from humanity's acoustic engagement with nature. The misinterpretation of this genesis—particularly in theological accounts—has fostered cognitive dependency that now manifests in modern crises of meaning and AI's disembodied language models.